A retrospective multicenter study on the efficacy and safety of disitamab vedotin monotherapy versus combination with anti-PD-1 immunotherapy in advanced gastric cancer - Shuailei Dong; Chen Wei; Xueting Wang; Xinyi Yang; Wei Shen; Shuyi Li; Jiye Xu; Yijie Ma; Liangyu Bie; Wenyue Yu; Ning Li (Scientific Reports)
Abstract Novel therapeutic agents including disitamab vedotin (RC48, an antibody-drug conjugate) and immune-checkpoint inhibitors (e.g., PD-1 inhibitors) have provided new hope as an advanced gastric-cancer (GC) treatment. This multicenter retrospective study studied RC48 monotherapy (MT)’s efficacy and safety against its combination with anti-PD-1 immunotherapy (IT) in advanced GC. Patients treated with RC48 MT or RC48 combined with anti-PD-1 IT from July 2021 to April 2023 were recruited for the study. The progression-free survival (PFS), overall survival (OS), objective-response rate (ORR), disease-control rate (DCR), and safety were studied. After propensity score matching (PSM) (1:1), this study included 34 in the RC48 plus anti-PD-1 IT group and 34 in the RC48 MT group. The median PFS was significantly longer in the combination-therapy (CT) group than in the MT group (5.3 versus 3.8 months, HR: 0.51, 95% CI: 0.31–0.85, p = 0.010), and the median OS was also notably increased (10.0 versus 6.8 months, HR: 0.45, 95% CI: 0.27–0.77, p = 0.003). The ORR and DCR were higher in the combination group (41.18% versus 14.71%, p = 0.031; 61.76% versus 35.30%, p = 0.052). Moreover, subgroup analyses further revealed that those in the CT group experienced a longer PFS and OS, particularly those with high HER2 expression or a PD-L1 CPS score of 1 or higher. The combination therapy (CT) achieved acceptable tolerability and manageable adverse events. Furthermore, the most common grade 3–5 treatment-related adverse events (TRAEs) included decreased white-blood-cell (WBC) count, decreased neutrophil count, and anemia. No new safety risks were observed. In sum, the RC48 and anti-PD-1 IT combination showed good efficacy and a manageable safety profile, indicating its strong potential as an advanced GC therapeutic option.